Respon Morfologi Daun Samawuang (Pangium edule Reinw.) pada Kondisi Lingkungan yang Berbeda - Syerina Febriani; Vauzia; Filza Yulina Ade; Reki Kardiman (Universitas Cokroaminoto Palopo, 2026)
Samawuang (Pangium edule Reinw.) is a tree that has economic value and potential as a food source, but its existence is decreasing due to lack of cultivation and changes in environmental conditions. Environmental factors such as altitude, temperature, humidity, rainfall, and soil conditions are known to affect plant growth, especially in leaf organs that are sensitive to environmental changes. Based on this, a study was conducted to investigate the morphological response of samawuang leaves under different environmental conditions. The study was conducted from December 2025 to January 2026 in two locations, namely Dharmasraya (131 mdpl) and Solok (409–467 mdpl). The method used was descriptive research with a quantitative approach by taking 20 leaf samples at each location which were analyzed using a t-test at a significance level of 5%. Parameters observed included leaf length, leaf width, leaf stalk length, and number of leaf veins. The results showed that there were significant differences in leaf length and width between the two locations. The average leaf length in Dharmasraya was higher at 41.20 cm compared to Solok at 30.20 cm, while the average leaf width in Dharmasraya was 34.05 cm higher than Solok at 25.71 cm. Meanwhile, the length of the leaf stalk and the number of leaf veins did not show significant differences. This study shows that Pangium edule R. has significant variations in leaf morphology adaptation to different environmental conditions.